Simulation of The Effect of Blank Geometry Toward The Mecanical Properties of Strains And Stress on Deep Drawing Process Using Material Aluminum 7075 - Pratama, Adjie Yoga; Widyasari, Auzini; Fakhruddin, Muhammad; Muzaki, Mochamad; Firmansyah, Hilmi Iman (PT. ELSHAD TECHNOLOGY INDONESIA, 2023)
Using Aluminum 7075 at a high temperature of 50 degrees Celsius, this study examines the effect of various blank geometry angles on the mechanical properties of strain and stress during the deep drawing process. This study systematically examines the impact of different blank geometry angles on the deformation behavior, strain distribution, and stress concentration during the deep drawing process of Aluminum 7075 sheet using a numerical simulation approach. To describe the behavior of the material against the effect of the angle on the pressure in the simulation taking into account realistic parameters, the main point is the result of the pressure treatment of the predetermined angle on the results of the strains and stresses created. The obtained results, which include strain distribution, stress concentration, and overall mechanical reaction, provide important information for the choice of the best blank geometry angle in deep drawing of Aluminum 7075 at high temperatures. This research contributes to the advancement of process optimization in the metal forming industry, providing a solid foundation for improving efficiency and quality in deep drawing operations involving high-strength aluminum alloys.